Antioxidative and Antiglycative Stress Activities of Selenoglutathione Diselenide - Akiko Kanamori; Nana Egawa; Suyako Yamasaki; Takehito Ikeda; Marcia Juciele da Rocha; Cristiani Folharini Bortolatto; Lucielli Savegnago; César Augusto Brüning; Michio Iwaoka (MDPI AG, 2024)
The damage caused by oxidative and glycative stress to cells accumulates on a daily basis and accelerates aging. Glutathione (GSH), a major antioxidant molecule in living organisms, plays a crucial role in detoxifying the stress-causing substances inherent in cells, such as H2O2 and methylglyoxal (MG), an important intermediate of advanced glycation end-products (AGEs). In this study, we focused on the enhanced antioxidant capacity of the selenium analog of GSH, i.e., selenoglutathione (GSeH), compared to GSH, and examined its effects on the detoxification of stress-causing substances and improvement in cell viability. In cell-free systems, GSeH (1 mM) generated in situ from GSeSeG in the presence of NADPH and glutathione reductase (GR) rapidly reduced more than 80% of 0.1 mM H2O2, indicating the significant glutathione peroxidase (GPx)-like antioxidant activity of GSeSeG. Similarly, around 50% of 0.5 mM MG was degraded by 0.5 mM GSeH within 30 min through a non-enzymatic mechanism. It was also found that GSeSeG (0.05-0.5 mM) showed glutathione S-transferase (GST)-like activity against 1-chloro-2,4-dinitrobenzene (CDNB), a model substance of oxidative stress-causing toxic materials in cells. Meanwhile, HeLa cells that had been pre-treated with GSeSeG exhibited increased viability against 1.2 mM H2O2 (at [GSeSeG] = 0.5-50 μM) and 4 mM MG (at [GSeSeG] = 3 μM), and the latter effect was maintained for two days. Thus, GSeSeG is a potential antioxidant and antiglycative stress agent for cells.